Self-management of Elderly with COVID-19 Pneumonia after Discharge from the Hospital. - Fuangmanakul, Kulitsara; Takaree, Sukrita (Journal of Nursing, Siam University, 2025)
The current outbreak of the coronavirus (COVID-19) is spreading rapidly. Most patients with COVID-19 Pneumonia are elderly. This Qualitative research studies aimed to study the Self-management of elderly with COVID-19 pneumonia after discharge from the hospital by applying the concept of self-management from Creer in nursing to the context of the elderly. Data was collected from November 2022 to April 2024. The interview consisted of 1) questionnaire on personal data such as gender, age, education level, status, occupation, monthly income, residence, and underlying diseases. 2) Assessment of self-management of the elderly. 3) Inquiry into self-management of the elderly. 4) Assessment of follow-up of symptoms of elderly with COVID-19 Pneumonia after discharge from the hospital. A specific sample of 30 people aged 60 years and over was selected. Symptoms were followed up twice after discharge: the first interview was for 3 months, and the second interview was for 6 months. The researcher analyzed the data: 1) General data using descriptive statistics, percentages, means, and standard deviations; 2) Data was collected and analyzed according to the conceptual framework. Self-management of elderly with COVID-19 Pneumonia after discharge from the hospital was good. The results showed that: The concept of Self-Management has been applied to nursing care for the Self-management of elderly with COVID-19 Pneumonia after discharge from the hospital. When returning home, they can live their daily lives with quality and reduce the risk of long-term complications.